2015
DOI: 10.1016/j.drugalcdep.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MAO inhibition and a combination of minor alkaloids, β-carbolines, and acetaldehyde on nicotine self-administration in adult male rats

Abstract: Introduction Although nicotine is the primary reinforcing constituent in cigarettes, there is evidence that other constituents in cigarette smoke may interact with nicotine to reinforce smoking behavior. Methods The present experiments investigated whether a novel combination of these cigarette smoke constituents would increase nicotine self-administration in adult male rats. The constituents included five minor alkaloids (anabasine, nornicotine, cotinine, myosmine, and anatabine), two β-carbolines (harman a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…Nicotine reduction is not intended to address all the reasons people smoke, but instead targets the neuropharmacological effects of combusted tobacco that are widely believed to be responsible for dependence. Although some other constituents of tobacco are psychoactive, current evidence from animal studies suggests that these other constituents, in the doses found in tobacco, would have little impact on behaviour either alone or in combination with low doses of nicotine 48. One non-nicotine effect of tobacco smoke—inhibition of monoamine oxidase—may increase sensitivity to the reinforcing effects of low doses of nicotine, but this effect does not appear to be sufficient to maintain rat self-administration if nicotine is adequately reduced 49.…”
Section: Common Questionsmentioning
confidence: 99%
“…Nicotine reduction is not intended to address all the reasons people smoke, but instead targets the neuropharmacological effects of combusted tobacco that are widely believed to be responsible for dependence. Although some other constituents of tobacco are psychoactive, current evidence from animal studies suggests that these other constituents, in the doses found in tobacco, would have little impact on behaviour either alone or in combination with low doses of nicotine 48. One non-nicotine effect of tobacco smoke—inhibition of monoamine oxidase—may increase sensitivity to the reinforcing effects of low doses of nicotine, but this effect does not appear to be sufficient to maintain rat self-administration if nicotine is adequately reduced 49.…”
Section: Common Questionsmentioning
confidence: 99%
“…MAO inhibition has been shown to increase nicotine self-administration on fixed-ratio (FR) and progressive-ratio schedules (Guillem et al, 2005;Smith et al, 2015;Villegier et al, 2007). However, the high doses of TCP used by some researchers have been shown to increase nicotine self-administration through acute, off-target effects (eg, monoamine release) rather than the long-lasting effect of MAO inhibition (Lotfipour et al, 2011;Villegier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although MAO inhibition clearly increases the primary reinforcing effect of nicotine under some conditions (Guillem et al, 2005;Smith et al, 2015), more research is needed. First, the impact of MAO inhibition across different nicotine doses is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical consideration for ongoing research will be a closer examination of gender differences and their influence on stress-mediated relapse. Indeed, emerging data from multiple studies continue to provide evidence for gender-specific differences in successful quit attempts in smokers [19] as well as sex-specific effects regarding the role of stress in nicotine use and relapse in preclinical models and in humans [261-263]. Evidence from smokers suggests that men are more sensitive to the pharmacological effects of nicotine, where women are more sensitive to smoking-related cues [264, 265], and these gender differences have important implications for smoking relapse and cessation strategies [266].…”
Section: Concluding Remarks and Future Considerationsmentioning
confidence: 99%